Improving the quality of steamed bread with whole soybean pulp: Effects of ultrasonic treatment on protein structure and reduction of beany flavor - Feng Han; Jialin Song; Mingming Qi; Yueming Li; Mei Xu; Xin Zhang; Chuangshuo Yan; Shanfeng Chen; Hongjun Li (Ultrasonics Sonochemistry)
Incorporation of whole soybean pulp (WSP) into wheat flour has been shown to improve the nutritional profile of steamed bread. However, this substitution often disrupts the protein network and introduces an undesirable beany flavor, compromising the overall quality of the steamed bread. This research explored the impacts of varying ultrasonic power levels on the quality of steamed bread containing WSP (WSPSB), with the goal of improving both the protein network structure and the flavor profile. The findings indicated that at an ultrasonic power of 300 W, WSPSB had an 18.10 % decrease in hardness and a 14.93 % increase in specific volume compared to the 0 W. Results from CLSM, SDS-PAGE, fluorescence intensity, surface hydrophobicity, and FTIR spectroscopy revealed that ultrasonic treatment modified the secondary protein structure by increasing the proportion of β-sheets and random coils. These changes facilitated better integration of soybean protein and gluten, thereby strengthening the steamed bread’s protein network. Furthermore, analyses of volatile flavor components, molecular docking, and correlation studies indicated that alterations in the protein structure mitigated the binding of beany flavor components to proteins, leading to significant reductions in their presence—specifically, a 7.12 % decrease in 1-Octen-3-ol and an 8.47 % decrease in Furan, 2-pentyl-. Overall, ultrasound treatment effectively refined the protein network and mitigated the beany flavor in steamed bread, thereby improving its quality.